THE IMPORTANCE OF PERIODONTAL THERAPY IN PATIENTS WITH ASSOCIATED SYSTEMIC DISEASES. CASE REPORT - Mihaela Moisei; Mariana Păcurar; Simina Chelărescu; Mioara Decusară (Romanian Society of Oral Rehabilitation, 2023)
Aim : this paper highlights the importance of a complex oral rehabilitation treatment within a multidisciplinary team for a patient with chronic marginal periodontal stage IV pathology associated with gingival overgrowths and correlative systemic pathology. Material and method: is analyzed the case of a 45-year-old female patient who requested dental treatment for gingival inflammation with gingivorragia, gingival overgrowths, dental mobility and malpositions of incisors, on the background of general status affected by obesity, type II diabetes mellitus and hypertension. To establish the diagnosis and the complex treatment plan was performed local clinical examination (inspection, palpation and periodontal probe-PD), orthopantomography (for the assessment of alveolar bone lysis) and blood analysis. Results: The evolution of the periodontal status was favorable following local procedures applied (guided microbial plaque therapy, closed-field periodontal curettage, laser removal of residual gingival hyperplasia) under general antibiotic protection, and radiological, the level of bone atrophy remained constant 4 years after the start of treatment. The periodontal disease stabilized with a good prognosis during the monitoring period and a positive impact on the general status as well. Conclusions: Adequate control of periodontal disease, with correct dental hygiene and appropriate multidisciplinary treatment can have a positive impact on systemic conditions, greatly improving the patient's quality of life.